Characterization of cis-acting elements regulating transcription from the promoter of a constitutively active rice actin gene. - Wang, Y (1992)
The promoter of the constitutively expressed rice (Oryza sativa) actin 1 gene (Act1) is highly active in transformed rice plants (W. Zhang, D. McElroy, and R. Wu, Plant Cell 3:1150-1160, 1991). A region 834 bp upstream of the Act1 transcription initiation site contains all the regulatory elements necessary for maximal gene expression in transformed rice protoplasts (D. McElroy, W. Zhang, J. Cao, and R. Wu, Plant Cell 2:163-171, 1990). We have constructed a series of Act1 promoter deletions fused to a bacterial beta-glucuronidase reporter sequence (Gus). Transient expression assays in transformed rice protoplasts, as well as transformed maize cells and tissues, identified two distinct cis-acting regulatory elements in the Act1 promoter. A 38-bp poly(dA-dT) region was found to be a positive regulator of Act1 promoter activity. Deletion of the poly(dA-dT) element lowered Gus expression by at least threefold compared with expression produced by the full-length Act1 promoter. By gel retardation and footprinting, we identified a ubiquitous rice protein which specifically recognizes this poly(dA-dT) element in the constitutively active Act1 promoter. A CCCAA pentamer repeat-containing region was found to be a negative regulator of the Act1 promoter in transformed rice protoplasts. Transient expression assays in different maize cells and tissues with use of the Act1 deletion constructs suggested that the CCCAA pentamer repeat region functions in a complex tissue-specific manner. A CCCAA-binding protein was detected only in root extracts.